Sensitive Detection of Ambient Formaldehyde by Incoherent Broadband Cavity Enhanced Absorption Spectroscopy - Jingwei Liu; Xin Li; Yiming Yang; Haichao Wang; Cailing Kuang; Yuan Zhu; Mindong Chen; Jianlin Hu; Limin Zeng; Yuanhang Zhang (Analytical Chemistry, 2020)
Formaldehyde (HCHO) is the most abundant atmospheric carbonyl compound and plays an important role in the troposphere. However, HCHO detection via traditional incoherent broadband cavity enhanced absorption spectroscopy (IBBCEAS) is limited by short optical path lengths and weak light intensity. Thus, a new light-emitting diode (LED)-based IBBCEAS was developed herein to measure HCHO in ambient air. Two LEDs (325 and 340 nm) coupled by a Y-type fiber bundle were used as an IBBCEAS light source, which provided both high light intensity and a wide spectral fitting range. The reflectivity of the two cavity mirrors used herein was 0.99965 (1 - reflectivity = 350 ppm loss) at 350 nm, which corresponded with an effective optical path length of 2.15 km within a 0.84 m cavity. At an integration time of 30 s, the measurement precision (1 sigma) for HCHO was 380 parts per trillion volume (pptv), and the corresponding uncertainty was 8.3%. The instrument was successfully deployed for the first time in a field campaign and delivered results that correlated well with those of a commercial wet-chemical instrument based on Hantzsch fluorimetry (R2 = 0.769). The combined light source based on a Y-type fiber bundle overcomes the difficulty of measuring ambient HCHO via IBBCEAS in near-ultraviolet range, which may extend IBBCEAS technology to measure other atmospheric trace gases with high precision.